2019
DOI: 10.3389/fimmu.2019.00687
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Antigen Presentation by HLA-DR+ NKG2C+ Adaptive NK Cells Specifically Activates Polyfunctional Effector Memory CD4+ T Lymphocytes

Abstract: Natural killer (NK) cells play a dual role in the defense against viral pathogens by directly lysing infected cells as well as by regulating anti-viral T cell immunity. Infection by human cytomegalovirus (HCMV) promotes a persistent expansion of NKG2C+ adaptive NK cells which have been shown to display enhanced antibody-dependent responses against infected targets and associated to viral control in transplanted patients. Based on gene expression data showing increased transcription of CIITA and several genes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 62 publications
6
70
0
Order By: Relevance
“…Nonetheless, given the plasticity of hematopoiesis described above, we believe that it's likely that some fraction of lineage-committed NK cells in humans derive from myeloid precursors. This notion is supported by other studies showing that under certain circumstances NK cells can share properties with DCs, such as MHC class II upregulation and antigen-presentation (54, 55). Conversely, there are conditions under which DCs acquire cytotoxicity characteristic of NK cells (56).…”
Section: Evidence For a Non-linear Model Of Nk Cell Developmentsupporting
confidence: 64%
“…Nonetheless, given the plasticity of hematopoiesis described above, we believe that it's likely that some fraction of lineage-committed NK cells in humans derive from myeloid precursors. This notion is supported by other studies showing that under certain circumstances NK cells can share properties with DCs, such as MHC class II upregulation and antigen-presentation (54, 55). Conversely, there are conditions under which DCs acquire cytotoxicity characteristic of NK cells (56).…”
Section: Evidence For a Non-linear Model Of Nk Cell Developmentsupporting
confidence: 64%
“…The role of HLA-DR on NK cells is still unclear. HLA-DR expression has been posited as a marker of NK cell activation but it has also been shown to play a role in immune modulation ( 47 ), though it has also been suggested that while HLA-DR+ NK cells are less phenotypically mature they still display high functional activity ( 48 ). While we did not see a statistically significant increase in frequencies of CD49a − e + NK cells in the livers of acute SIV-infected macaques relative to naïve animals, the small increasing trend may be interesting to explore in further studies with a larger animal cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive transfer of HCMV CD4 + T cells demonstrated the antiviral roles of virus-specific CD4 + T cells against murine CMV in immunocompromised mice [102,103]. Recently a subset of HCMV specific effector CD4 + T cells has been described that directly responses to the viral infection [104]. Moreover, CD4 + helper T cell function is required for the persistence of cytotoxic activity of adoptively transferred CD8 + T cells in recipients of allogeneic bone marrow transplants [105].…”
Section: Host Responses To Hcmv Infectionmentioning
confidence: 99%